LTE Network Planning in Current Co-Existing GSM/TD-SCDMA/WLAN Systems - Wei Liu; Haiyan Chen (Dianxin kexue)
To build LTE network in current co-existing GSM／TD-SCDMA／WLAN mobile systems, integrated planning for these 4 co-existing system is needed, which is important for accurate LTE planning and benefit for efficiency improvement and cost decreasing of the network deployment, also it is benefit for improvement of the network quality and QoE of customers. The integrated modeling based on different wireless environment and scenarios were analyzed, and the mentality, method and techniques for LTE network planning in current co-existing GSM／TD-SCDMA／WLAN mobile systems were provided.